The EU and MERCUSOR exchange tariff offers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
On March 5th 2003 it was announced that the EU and Mercusor had now exchanged...